Preclinical and Clinical Sex Differences in Antipsychotic-Induced Metabolic Disturbances: A Narrative Review of Adiposity and Glucose Metabolism. Issue 4 (2019) - Castellani, Laura N.; Costa-Dookhan, Kenya A.; McIntyre, William B.; Wright, David C.; Flowers, Stephanie A.; Hahn, Margaret K.; Ward, Kristen M.
No abstract available